DOMINASI MAKSIM KESEDERHANAAN PADA KESANTUNAN BERBAHASA ANAK PEKERJA BURUH DI SD 03 TENGGELES - Ulum, Siti Nurul Miftahul; Kironoratri, Lintang (STKIP Persada Khatulistiwa Sintang, 2024)
The aim of this research is to describe the implementation of politeness maxims at class V in SD 3 Tenggeles. This research applied qualitative research with a descriptive method of a case study approach. The primary data sources in this research are students, teachers and parents. While secondary data are books and publications of relevant studies. Data collection techniques are observation, interviews, documentation. The analysis used in this research refers to the Miles and Hubernam concept, namely data collection, data reduction, data presentation, and drawing conclusions. The results of this study show that parents' work influences on children's language politeness. From the six politeness maxims, there are some students who have fulfilled them, but there are also those who have not fulfilled them. One of the politeness maxims which is fulfills the most is the maxim of simplicity.